The Temple in early Christianity experiencing the sacred - Regev, Eyal 1970- (New Haven, CT Yale University Press, 2019)
A comprehensive treatment of the early Christian approaches to the Temple and its role in shaping Jewish and Christian identity The first scholarly work to trace the Temple throughout the entire New Testament, this study examines Jewish and Christian attitudes toward the Temple in the first century and provides both Jews and Christians with a better understanding of their respective faiths and how they grow out of this ancient institution. The centrality of the Temple in New Testament writing reveals the authors’ negotiations with the institutional and symbolic center of Judaism as they worked to form their own religion
Frontmatter -- Contents -- Preface -- Editions and Translations -- Introduction -- 1. Jesus: “Cleansing,” Trial, and Last Supper -- 2. Paul’s Letters: Temple Imagery as Religious Identity -- 3. Mark: Criticism or Rejection? -- 4. Q and Matthew: The Sacred Temple -- 5. Luke–Acts: Living and Dying with the Temple -- 6. The Gospel of John: Temple and Christology -- 7. The Book of Revelation: The Alternative Temple -- 8. Hebrews: The New Heavenly Temple Cult Based on the Old One -- 9. Relating to Judaism, Experiencing the Sacred -- 10. Concluding Thoughts -- Notes -- Bibliography -- General Index -- Index of Ancient Sources
[Online-Ausg.]
Mode of access: Internet via World Wide Web.
In English
Keywords: Christianity -- Early works to 1800; RELIGION / General; RELIGION / Biblical Studies / History & Culture